An effective, facile, and rapid synthesis of nanosized Mn3O4 using a microwave route - Yadav, Akash; Jha, Ratnesh; Bhatkar, Akash; Kamble, Aditi; Vaishnav, Vishal; Bogalera, Shivamurthy P.; Manikandan, Marimuthu; Nayaka, Girish Praveen; Umbarkar, Shubhangi; Raja, Thirumalaiswamy; Bhatte, Kushal D. (Journal of Nanoparticle Research, 2024)
Microwave-assisted one-pot, one-step, calcination-free synthesis of nanosized Mn3O4 is reported using only benzylamine and manganese acetate. Benzylamine in this protocol plays a vital role for efficient microwave synthesis. This microwave method enables the synthesis of nanosized Mn3O4 in just few hours only in a single step eliminating the need of calcinations of any intermediate. The synthesized nanosized Mn3O4 was analyzed by XRD, HRTEM, EDAX, and Raman spectroscopy. The catalytic and electrochemical properties of as-synthesized Mn3O4 were investigated. In galvanostatic charge-discharge experiments, after 800 cycles, more than 89% capacitance was retained for electrodes made by as synthesized Mn3O4 nanomaterials indicating its very good stability. In the catalytic conversion of cinnamyl alcohol to cinnamaldehyde via oxidation, using as prepared nanosized Mn3O4 as a catalyst, it displays effective catalytic properties. A probable mechanical study of its formation was also envisaged. This synthesis protocol is additive-free, occurs in a short time, is facile, is energy efficient, and eliminates the use of many chemicals. These silent features make these reported protocols economically viable and environmentally benign which adhere to the principles of Green Chemistry.
Keywords: Calcination free; Electrochemical and catalytic properties; Nanosized Mn3O4; Single-step synthesis

Facile and eco-friendly synthesis of Mn2O3 nanoparticles via microwave-assisted glycerol-thermal method - Yadav, Akash; Jha, Ratnesh; Bhatkar, Akash; Gehlot, Bhavika; Kamble, Aditi; Manikandan, Marimuthu; Bhosale, Hritvik; Vaishnav, Vishal; Rathod, Rutik; Umbarkar, Shubhangi; Raja, Thirumalaiswamy; Bhatte, Kushal D. (Journal of Chemical Sciences, 2025)
Microwave-assisted efficient synthesis of nanosized manganese oxide (Mn2O3) is reported using glycerol and manganese acetate. Glycerol in this reported methodology acts as an efficient solvent for this nanomaterial synthesis under microwave radiation. This reported method enables the synthesis of nanosized Mn2O3 without further use of additives, stabilizers, and bases other than glycerol and manganese precursor. Glycerol is a renewable biomaterial derived nonvolatile and nontoxic, safe solvent. It has a high boiling point and dielectric constant, which makes it an ideal solvent for microwave synthesis. The synthesized nanosized Mn2O3 was analyzed by X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), and Raman spectroscopy. We examined the catalytic properties of as-synthesized Mn2O3 for cinnamyl alcohol oxidation to cinnamaldehyde. In this oxidation activity experiment, nanosized Mn2O3 exhibits good conversion and selectivity towards the desired product. We also made an attempt to understand the probable mechanism of nanomaterial formation and found some conclusive evidence to support it. This research methodology is facile, energy efficient, and involves minimum chemicals for synthesis. It makes this reported methodology not only economically attractive but also environmentally friendly, which aligns well with green chemistry principles.
Keywords: Glycerol; green chemistry; Nanosized Mn2O3; nanostructured catalysis

An unique microwave-assisted approach for synthesis of nanosized Fe3O4 as a catalyst in transfer hydrogenation of furfural - Bhatkar, Akash; Yadav, Akash; Gehlot, Bhavika; Rathod, Rutik; Mane, Samruddhi; Gawande, Vaishnavi; Bhosale, Hrtivik; Raja, Thirumalaiswamy; Bhatte, Kushal D. (Research on Chemical Intermediates, 2025)
In this manuscript, we report an unique, one pot, one step synthesis of Fe3O4 nanoparticles. The protocol for synthesis of nanosized Fe3O4 was developed using only Benzyl Amine and Fe(II)acetate precursor via microwave route. Microwave route enables the synthesis of Fe3O4 nanoparticles in short duration and eliminates the need of several chemicals. These salient features make the entire synthetic process environment benign as per green chemistry principles. The morphology and other properties of synthesized nanoparticles were studied by using X-ray diffraction (XRD), X-ray photoelectron spectroscopy analysis (XPS), Raman spectroscopy, Field Emission Scanning Electron Microscopy (FE-SEM), and High-Resolution-Transmission Electron Microscopy (HR-TEM). As-synthesized Fe3O4 nanoparticles exhibit efficient catalytic transfer hydrogenation of furfural using isopropanol as the solvent and hydrogen source, and provide furfuryl alcohol in good yield. This nanosized Fe3O4 was easily removable using magnet and exhibits good reusability. It is observed that acidic-basic sites of nanosized Fe3O4 play a vital role in catalytic transfer hydrogenation reaction.
Keywords: catalytic transfer hydrogenation; Furfural to furfuryl alcohol; green synthesis; Magnetically separable catalyst; Nanosize Fe3O4